ANALISIS KOROSI TERHADAP PERFORMA BUTTERFLY VALVE PADA SISTEM BONGKAR MUAT CARGO DI MT.ADRIA - Gema Fajrul Akbar; Bayu Yudho Baskoro; Rizal Rochmansyah; Dody Efrianto; Akhmad Gifari Multazam (STKIP Subang, 2026)
Corrosion is one of the primary causes of failure in ship piping systems, particularly on butterfly valves, which play a critical role in the loading and discharging operations of liquid cargo. This study aims to analyze the causes of corrosion on butterfly valves and its impact on the operational performance of the cargo discharge system aboard the MT.Adria. dopts a descriptive qualitative approach, with data collected through field observations, interviews with crew members, and documentation. The findings show that valve damage is caused by a combination of harsh marine environmental conditions, inappropriate material selection that leads to galvanic corrosion, and inadequate maintenance procedures. This corrosion results in valve malfunction, system leakage, and delays in cargo discharge operations. Using a fishbone diagram analysis, the study identifies three main contributing factors: valve material, operational environment, and inspection and maintenance practices. The findings highlight that a small component failure, such as a valve, can significantly affect the overall efficiency and safety of ship operations. The study recommends implementing risk-based preventive maintenance, selecting corrosion-resistant valve materials suitable for marine environments, and conducting routine inspections to enhance the reliability of the cargo discharge system on tankers.